2010
DOI: 10.1007/s00894-010-0832-3
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity balance, π-electron cooperativity and H-bonding properties in tautomerism of salicylideneaniline: the quantum theory of atoms in molecules (QTAIM) approach

Abstract: Topological analysis based on DFT calculations regarding proton transfer reaction in salicylideneaniline (SA) was performed to scrutinize possible changes in the intramolecular H-bond, π-electron delocalization and aromaticity levels of certain fragments. Quantum chemical calculations and natural bond orbital (NBO) analyses were carried out over a tautomeric ensemble whose members correspond to the molecules at different stages in tautomeric interconversion of SA. The elaboration of intramolecular hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 79 publications
3
24
0
1
Order By: Relevance
“…Aromatic Schiff bases are one of the most promising chemical species to be considered for this purpose because of their structural and electronic properties mentioned below. The structures of ortho-hydroxy aromatic Schiff bases, in particular salicylideneaniline (SA) derivatives, have received much attention owing to their keto-phenol (or NH OH) tautomerism (Fabian et al, 2004;Amimoto & Kawato, 2005;Filarowski, 2005;Filarowski et al, 2005;Petek et al, 2008Petek et al, , 2010Karabiyik et al, 2009Karabiyik et al, , 2011. Depending on the position of the tautomeric proton, two types of intramolecular hydrogen bonds are possible, O-HÁ Á ÁN and OÁ Á ÁH-N, in phenol (OH) and in cisketo (NH) tautomers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic Schiff bases are one of the most promising chemical species to be considered for this purpose because of their structural and electronic properties mentioned below. The structures of ortho-hydroxy aromatic Schiff bases, in particular salicylideneaniline (SA) derivatives, have received much attention owing to their keto-phenol (or NH OH) tautomerism (Fabian et al, 2004;Amimoto & Kawato, 2005;Filarowski, 2005;Filarowski et al, 2005;Petek et al, 2008Petek et al, , 2010Karabiyik et al, 2009Karabiyik et al, , 2011. Depending on the position of the tautomeric proton, two types of intramolecular hydrogen bonds are possible, O-HÁ Á ÁN and OÁ Á ÁH-N, in phenol (OH) and in cisketo (NH) tautomers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…al 129. studied aromaticity balance, π-electron cooperativity and H-bonding properties in tautomerism of salicylideneaniline and found that delocalization in chelate chain estimated by PDI130 correlates with H-bond strength.…”
mentioning
confidence: 99%
“…This is an intriguing aspect implying aromaticity balance between six‐membered and five‐membered rings of dibenzothiophene as compared with dibenzofuran. Aromaticity balance is a well‐known mechanism involving intramolecular electronic charge transfer . Inclusion of selenium as endocyclic heteroatom in dibenzofuran skeleton makes central five‐membered ring considerably aromatic, while inclusion of tellurium leads to a deficiency in the aromaticity of five‐membered ring without considerable changes in aromaticities of two flanking benzenes.…”
Section: Resultsmentioning
confidence: 99%
“…Aromaticity balance is a well-known mechanism involving intramolecular electronic charge transfer. [44,45] Inclusion of selenium as endocyclic heteroatom in dibenzofuran skeleton makes central five-membered ring considerably aromatic, while inclusion of tellurium leads to a deficiency in the aromaticity of five-membered ring without considerable changes in aromaticities of two flanking benzenes. Selenium and tellurium are distinguished from other chalcogens by the presence of fully occupied dorbitals.…”
Section: Resultsmentioning
confidence: 99%